Design and fabrication of agriculture sprayer / Arif Hakimi Zainal Zulfikar - Zainal Zulfikar, Arif Hakimi (2023)
First of all, the objective of this product is to fertilize the plants and kill weeds at that farm. This project is suitable to be used by farmer in small farm or big farm. The design and fabrication of this product have some improvement that will ease their jobs to fertilize the plants and poison weeds. This product will increase rate of spraying the plants because the project design to have more nozzles compare to common sprayer that only has one nozzle. At this point, the project will spray large areas and faster that make this product work more efficient.